Preparation of Novel Polystyrene-Layered Hydroxide Zinc Benzoate Nanocomposites by Bulk Polymerization - Li, Xin; Yu, Honghao; Zhang, Houfang; Xue, Xiangxin (Asian Journal of Chemistry, 2015)
Novel polystyrene-layered hydroxide zinc benozate nanocomposites were prepared by bulk polymerization with azobisisobutyronitrile initiator. The well dispersion of layered hydroxide zinc benzoate in matrix was observed. The presence of filler shields polystyrene from thermal oxidation and brings to a reduction of 50 % in heat release rate during combustion with 1 wt. % loading. The research sucessfully exemplified the feasibility of layered hydroxide benzoate as fillers in polymeric nanocomposites.